Chemical Characterization of Protein Contentrates of Duckweed (Fanruily Lenrnnaceae) - Ismail, Maznah (Universiti Putra Malaysia Press, 1998)
The amount of protein was determined in supernatant and residual pulp of three species of duckweed, Spirodela Polyrrhiza, oligorrhiza, Wolffia columbiana and a mixed culture. Protein content of the supernatant and the residual pulp was similar except S. oligorrhiza in which the supernatant had triple the value. Maznah Ismail Precipitation studies with acid and organic solvents (acetone, isobutanol and isopropanol) showed that the amount of protein precipitated varied with the solvent used. On average, only about 20% protein was precipitated from the supernatant. More protein was precipitated by acid (pH 5.8) and isopropanol (5% v/v). Amino acid analysis showed that the essential amino acid content of the whole frond, supernatant and pulp compared favourably with human and cow's milk, egg and FAO reference pattern, with the exception of methionine. Fractionation of the soluble material using Sephacryl S-200 and Sephadex G-50 yielded six components except S. oligorrhiza, which yielded seven components. The first component was> 250,000 daltons in size and the last two < 10,000. Further fractionation by anion exchanger, DJ<.AE Sepharose CL-6B yielded 12 components, except W columlbiana, which had 9. The first three components had net positive charge while the rest had net negative change. Anti-nutritional factors were also determined in two duckweed species (Spirodela polyrrhiza and Lemna perpusilla Torrey) and their protein concentrates. Anti-nutritional factors were found to be low; Spirodela polyrrhiza had higher values than Lemna perpusilla except for trypsin inhibitor. However analysis of variance showed no significant difference (p ~0.05) in the levels of these anti nutritional factors between the two species.